2019
DOI: 10.2174/0929867324666170523123010
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Aquaporins by Dietary Patterns and Plant Bioactive Compounds

Abstract: Healthful dietary patterns and bioactive compounds supplementation can be adopted as simple and easy intervention to prevent, attenuate or cure clinical disorders, especially when it comes degenerative and chronic diseases. In the recent years, a growing body of evidence indicates Aquaporins (AQPs), a family of membrane channel proteins widely expressed in the human body, among the targets underlying the beneficial action played by some food nutrients and phytochemical compounds. Here, we provide an overview o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 83 publications
0
12
0
Order By: Relevance
“…The results are not surprising, in light of recent findings on the beneficial effect of polyphenols, and phytochemical compounds in general, in modulating AQPs gene expression (for a complete review see [ 48 ]). Particularly, Kumar et al found that QUER treatment of streptozotocin-induced diabetic rats prevents the retina neurodegeneration, at least in part by normalizing the expression of AQP4 (inhibition) [ 49 ], even if it is not clear if this effect derives from its antioxidant activity or by preventing retinal edema.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…The results are not surprising, in light of recent findings on the beneficial effect of polyphenols, and phytochemical compounds in general, in modulating AQPs gene expression (for a complete review see [ 48 ]). Particularly, Kumar et al found that QUER treatment of streptozotocin-induced diabetic rats prevents the retina neurodegeneration, at least in part by normalizing the expression of AQP4 (inhibition) [ 49 ], even if it is not clear if this effect derives from its antioxidant activity or by preventing retinal edema.…”
Section: Discussionmentioning
confidence: 59%
“…Polyphenols have been shown to modulate AQPs expression, but so far, there was no data about their effects on the osmotic water permeability, or on the direct interaction with AQP/AQPs [ 48 ]. The results herein presented, suggest that not only the polyphenols QUER and NRG, but also ASME and MARR, are able to normalize the water permeability, which in turn determines the removal of H 2 O 2 and oxidative stress resolution.…”
Section: Discussionmentioning
confidence: 99%
“…Due to their diversity and food distribution the latest classification subdivides polyphenols in phenolic acids, curcuminoids, flavonoids, chalcones, stilbenes, lignans, and isoflavonoids (González-Castejón and Rodriguez-Casado, 2011 ; Upadhyay and Dixit, 2015 ). Bioactive polyphenols also influence the expression and biophysical properties of mammalian AQPs (Zhang et al, 2014 ; Fiorentini et al, 2015 ; Cataldo et al, 2017 ). The AQPs modulated by polyphenols and related health benefits are summarized in Table 1 .…”
Section: Dietary Polyphenols and Aquaporinsmentioning
confidence: 99%
“…As a polyphenol, resveratrol can also act as tyrosine kinases inhibitor and as a modulator of the mitogen activated protein kinase/extracellular signal-regulated kinase 1/2 (MEK-ERK1/2), mitogen-activated protein kinases (MAPK), activator protein 1 (AP-1), and NF-κB pathways in different tissues (Yu et al, 2001 ; Gao et al, 2004 ; Kundu et al, 2004 ). Resveratrol has been reported to influence the gene expression of various AQPs (see Cataldo et al, 2017 for a review). In human keratinocytes, AQP3 has been found to play a pivotal role in skin hydration, although overexpression of AQP3 is also linked with hyperplastic epidermal disorders (Nakahigashi et al, 2011 ).…”
Section: Dietary Polyphenols and Aquaporinsmentioning
confidence: 99%
“…As for T2D, structural analogs of HTS13286 featuring pharmacological and clinical sustainability offer worthy potential as new options in preventing end-stage liver disease, from simple steatosis to NAFLD/NASH and consequent liver fibrosis and hepatocarcinoma. Phytochemical modulation of AQP9 expression by nutraceutics counteracting excess hepatic lipid accumulation ( Cataldo et al, 2017 ; Tesse et al, 2018 ) is also worthy of investigation in preventing or improving prognosis of NAFLD/NASH. The heterocyclic compound HTS13286 is a selective and potent blocker of AQP9 with an IC 50 of 1.5 μM ( Jelen et al, 2011 ), however, its scarce water solubility hampers its use in vivo .…”
Section: Aquaglyceroporins As Drug Targets For Metabolic Diseasesmentioning
confidence: 99%